2010
DOI: 10.1093/aob/mcq190
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate drift promotes changes in fitness and transgene gene flow in canola (Brassica napus) and hybrids

Abstract: The results of this study demonstrate the potential for persistence of glyphosate resistance transgenes in weedy plant communities due to the effect of glyphosate spray drift on plant fitness. Additionally, glyphosate drift has the potential to change the gene-flow dynamics between compatible transgenic crops and weeds, simultaneously reducing direct introgression into weedy species while contributing to an increase in the transgenic seed bank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
2
57
0
1
Order By: Relevance
“…These experiments demonstrated that the genetic modification per se does not enhance ecological fitness. Ecophysiological experiments on comparative fitness between the GM plant and its non-GM counterpart and modelling did not indicate that genes conferring herbicide tolerance significantly alter the competitive ability of GM plants (Fredshavn et al, 1995;Warwick et al, 1999Warwick et al, , 2009Norris and Sweet, 2002;Claessen et al, 2005a,b;Simard et al, 2005;Londo et al, 2010). Beckie et al (2004) showed that GMHT oilseed rape with single or multiple herbicide tolerance traits is not more persistent (weedier) than non-GMHT plants.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments demonstrated that the genetic modification per se does not enhance ecological fitness. Ecophysiological experiments on comparative fitness between the GM plant and its non-GM counterpart and modelling did not indicate that genes conferring herbicide tolerance significantly alter the competitive ability of GM plants (Fredshavn et al, 1995;Warwick et al, 1999Warwick et al, , 2009Norris and Sweet, 2002;Claessen et al, 2005a,b;Simard et al, 2005;Londo et al, 2010). Beckie et al (2004) showed that GMHT oilseed rape with single or multiple herbicide tolerance traits is not more persistent (weedier) than non-GMHT plants.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…The progeny of hybrids of oilseed rape and wild relatives bearing the herbicide tolerance trait does not show any enhanced fitness, persistence or invasiveness, and behaves as their non-GM comparators, unless the herbicides for which tolerance has been obtained are applied (Londo et al, 2010;Watrud et al, 2011).…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…Consequently, transportation and handling activities during import of GM OSR are considered the main cause of unintended occurrence and establishment of feral GM OSR in countries without GM OSR cultivation. In these countries, import restrictions have been put into place because introgression of herbicide resistant transgenes may cause problems with weed management and may negatively affect the integrity of genetic resources in wild relatives (Londo et al, 2010).…”
Section: Oilseed Rape As a Model System For Seed Spillage Along Transmentioning
confidence: 99%
“…Secondly, because of herbicide resistance of GM oilseed rape, these feral plants establish preferentially in habitats where herbicides are applied or that are affected by spraying in adjacent areas. Due to herbicide application selection pressure supports survival of feral glyphosate resistant plants, and this may lead to an introduction of transgenes into related species (Londo et al, 2010) growing in habitats that have to be kept free of vegetation. Consequently, sprayed railway tracks pose an appropriate habitat for the establishment of herbicide resistant OSR as it was shown in Switzerland (Schoenenberger and D'Andrea, 2012).…”
Section: Perspectives On Safeguard Mitigation Of Seed Spillage On Lonmentioning
confidence: 99%
“…Experiments and models on fitness differences between the GM plant and its non-GM counterpart (category 2 above) are usually inferred from a composite measure of relative plant germination, emergence, growth, survivorship, biomass and fecundity (Fredshavn et al, 1995;Warwick et al, 1999Warwick et al, , 2004Warwick et al, , 2009Norris and Sweet, 2002; Claessen et al, 2005a,b;Simard et al, 2005;Londo et al, 2010). Beckie et al (2004) showed that GMHT oilseed rape with single or multiple HT traits is not more persistent (weedier) than non-GMHT plants.…”
Section: Impact -Would Ht Traits Alter Fitness Persistence and Invasmentioning
confidence: 99%